The natural history of idiopathic chronic large asymptomatic non-inflammatory pericardial effusions. (3rd October 2022) - Lazaros, G; Lazarou, E; Valatsou, A; Vlachopoulos, C; Antonopoulos, A S; Dimitroglou, Y; Sakalidis, A; Tsioufis, P; Kachrimanidis, I; Tsioufis, C
Abstract: Background/Introduction: Pericardial effusions (PEFs) are a challenging and often troublesome pericardial syndrome. The most recent 2015 ESC guidelines on pericardial diseases recommend drainage in cardiac tamponade or suspected bacterial/ neoplastic etiology (class IC), which should also be considered in large, idiopathic chronic PEFs. Purpose: In this work we assessed the natural history of asymptomatic, idiopathic, chronic, C-reactive protein (CRP) negative, large PEFs. Methods: We assessed retrospectively consecutive patients referred to the pericardial unit of our institution with idiopathic (without definite underlying etiology after extensive work-up), chronic (>3 months), large (maximal effusion diameter at end-diastole >2cm), asymptomatic, without evidence of ongoing pericardial inflammation (without CRP elevation or evidence of pericardial inflammation with cardiac magnetic resonance imaging) PEFs. To define the natural history of this condition, only patients with a follow-up of at least 2 years were included. The change in the PEF diameter from the first evaluation to the last follow-up namely: regression (complete or decrease from large to moderate/small), progression with symptoms appearance requiring drainage, or stability over time (defined as variation of PEF diameter <5mm, but still in the range of large), was assessed. Follow-up according to our institutional protocols was performed every 3 months and included clinical examination and focused echocardiography. Results: Thirty patients fulfilled the inclusion criteria and were analyzed. No patient was receiving anti-inflammatory treatment during follow-up. Nevertheless, 12 patients (40%) had received from their attending physicians a course of anti-inflammatory treatment (non-steroidal anti-inflammatory drugs, glucocorticoids, colchicine and combinations) before enrollment, without or with temporary results. The mean age of this study population was 64.9 (±16.1) years and the mean follow-up was 49.8 (±17.8) months. Women were numerically more often affected compared to men (57% vs. 43%, p=0.465). History of pericarditis was reported in 13% of cases. The mean maximal PEF diameter was 24.5mm (±3.3) and the median disease duration at first evaluation was 15.5 (7–57) months. Concerning outcome, the effusion size remained stable in 24 out of 30 patients (80%), regressed in 4 (13%, ) and increased in size requiring drainage due to symptoms onset in the remainder 2 (7%). During follow-up 2 patients (7%) with stable in size effusions died from non-cardiac causes. Conclusions: According to this study results the outcome of idiopathic, chronic, large, asymptomatic and without evidence of inflammation PEFs is overall favorable. Patients should be reassured about the benign course of this condition but at the same time, advised to seek medical care should symptoms appear, for a timely intervention with pericardial drainage. Funding Acknowledgement: Type of funding sources: None.